High Burden among Older Family Caregivers is Associated with High Prevalence of Symptoms: Data from the Swedish Study “Good Aging in Skåne (GÅS)” - Henrik Ekström; Nathalie Lundholm Auoja; Sölve Elmståhl; Lena Sandin Wranker (Journal of Aging Research)
Background/Aim. Certain groups of informal caregivers have been shown to have worse health compared to noncaregivers. The aim of this cross-sectional study was to explore the health and gender aspects of caregiving in an older Swedish population. Methods. Our study included 5457 participants from the longitudinal, general population study “Good Aging in Skåne.” A total of 33 self-reported symptoms were obtained from questionnaires and were then divided into seven domains: depressive, musculoskeletal, gastrourinary, symptoms related to head, cardiopulmonary, symptoms related to tension, and metabolic symptoms. Multivariate logistic regression analysis was performed to assess the risk of developing symptoms in each of the seven domains, regarding caregiving burden and caregiving in relation to gender. Results. We found that caregivers, compared to noncaregivers, had a higher prevalence for depressive and tension-related symptoms. High-burden caregivers exhibited significantly more individual symptoms and a higher prevalence of symptoms in the depressive, tension, and gastrourinary domains of symptoms compared to both low-burden caregivers and noncaregivers. More than 79% of high-burden caregivers reported general fatigue, and over half of the high-burden caregivers experience depressive mood. Female caregivers showed a significantly higher risk of reporting depressive symptoms (OR = 1.54, 95% CI 1.19–1.98) and tension-related symptoms compared to male caregivers. Conclusion. Depressive and tension-related symptoms were more common in caregivers, especially in high-burden caregivers. High-burden caregivers might be at a risk of adverse mental health, and this highlights the need to offer proper support to these groups.